METODOLOGIAS ACTIVAS EN EL PROCESO DE ENSEÑANZA APRENDIZAJE DE LOS NIÑOS Y NIÑAS DE SEPTIMO AÑO DEL CENTRO EDUCATIVO COMUNITARIO INTERCULTURAL BILINGUE JOSÉ ANTONIO PONTON ALAUSI PERIODO 2017-2018 - Sango Sango, Nelson Ernesto (2019)
The school inter-learning in the Bilingual Intercultural Community Educational Center "José Antonio Pontón". Seeks human growth in which the existing methodologies adequately applied to create an interest in learning become one of the most desired characteristics of the educational authorities with their teaching staff. However, despite the reforms legally implement in the Constitution of the Republic, the Education Law and the National Development Plan, considering that these aspects should strengthen the development of cognitive skills in the teaching-learning process. The objective of the investigation is to determine its importance and influence of the active Methodologies in the teaching-learning process, being necessary to structure it concretely in daily and innovative methods that allow the visibility of the pedagogical roles that Basic Education teachers have. The research methodology has a mixed approach, and its design is non-experimental, the types that identify and have applied are basic, field and bibliographic, descriptive, and correlational. The study population is those of the seventh year of the CECIB. Research and data processing techniques and instruments have applied that made it possible in practice to verify the objectives of the study. The conclusions and the expectations that created in the educational community can improve concerning the idea of overcoming through real experiences that encourage the development of knowledge, skills, abilities and other appropriate characteristics in the work of classroom to get meaningful learning.